Giant Plexiform Schwannoma of the Tongue. (21st September 2011) - Nisa, Lluís; von Büren, Toni; Tiab, Amine; Giger, Roland
Abstract : We present the case of a 38-year-old woman that presented with a very slowly enlarging mass of the tongue. MRI revealed a large mass originating in the tongue base and extending to the supraglottic space. Biopsy of this tumor confirmed the diagnosis of schwannoma. An endaural approach allowed complete resection of the tumor. Definitive histopathological examination showed a plexiform schwannoma. Schwannoma or neurilemoma represents a benign tumor potentially affecting any nerve. The head and neck region is a relatively common location for schwannomas, but tongue schwannomas are considered to be rare and pose the problem of both clinical and histological differential diagnosis of tongue masses.